Digital Literacy and Cultural Narratives for Social Sustainability in Primary Education Transformation - Assalamah, Tuhfatul Mubarokah; Hilza, Intan Fitri (IAIN Madura, 2025)
This study investigates the role of digital education in promoting social sustainability, cultural preservation, and equitable access to knowledge in the context of primary education. The research focuses on an Islamic primary school in East Java, Indonesia, which actively implements digital transformation through adaptive learning technologies, collaborative platforms, and digital humanities integration. The study aims to understand how these digital tools align with Sustainable Development Goals (SDGs), particularly in fostering inclusion and environmental responsibility. Employing a qualitative case study design, data were collected through semi-structured interviews, focus group discussions, and direct classroom observations involving 16 participants, including school leaders, teachers, parents, and program facilitators. The findings reveal that the integration of post digital aesthetics and sustainability initiatives supports inclusive and ethical educational practices, while also challenging deterministic views of technology. The study emphasizes that digital transformation in education must be culturally contextualized and ethically guided to ensure long-term impact. Future research is recommended to explore scalable models across diverse educational settings.